2014
DOI: 10.1021/am502298z
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Processing for Crystallization and Densification of Atomic Layer Deposition BaTiO3 Thin Films

Abstract: High-k, low leakage thin films are crucial components for dynamic random access memory (DRAM) capacitors with high storage density and a long storage lifetime. In this work, we demonstrate a method to increase the dielectric constant and decrease the leakage current density of atomic layer deposited BaTiO3 thin films at low process temperature (250 °C) using postdeposition remote oxygen plasma treatment. The dielectric constant increased from 51 (as-deposited) to 122 (plasma-treated), and the leakage current d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 32 publications
1
43
0
Order By: Relevance
“…Previously, plasma annealing or extensions of in-cycle plasma during PEALD have shown similar improvements in thin film properties of high k oxide-based dielectrics. 11 In this paper, we report on PEALD of SiN x films with three different precursor chemistries (TSA, tris(dimethylamino)silan (3DMAS), dichrolosilane (DCS)) and the WER performance achieved with each. In particular, we note the strong correlation found between film density and WER regardless of precursor chosen, PEALD reactor utilized, or variation of several process parameters.…”
Section: -2mentioning
confidence: 99%
“…Previously, plasma annealing or extensions of in-cycle plasma during PEALD have shown similar improvements in thin film properties of high k oxide-based dielectrics. 11 In this paper, we report on PEALD of SiN x films with three different precursor chemistries (TSA, tris(dimethylamino)silan (3DMAS), dichrolosilane (DCS)) and the WER performance achieved with each. In particular, we note the strong correlation found between film density and WER regardless of precursor chosen, PEALD reactor utilized, or variation of several process parameters.…”
Section: -2mentioning
confidence: 99%
“…For example, mostly amorphous BTO with embedded crystalline moieties that provides a good tradeoff between low leakage current and high dielectric constant cannot be characterized with conventional X-ray diffraction (XRD). 64,65 In the following sections, we will review the strategies that have been developed to date for achieving high-performance perovskite thin films using ALD, particularly for STO and BTO. In addition, we will outline the characterization techniques that provide insights into the structure, composition, and dielectric properties of ALD perovskites.…”
Section: Perovskite Phase In the Ultrathin-film Regimementioning
confidence: 99%
“…Intensive research has been conducted in the area of plasma utilization for intradeposition treatment of ALD perovskite films, mostly STO films (Table 3). 64,78,[81][82][83][84][85][86][87][88][89][90][91][92][93] Kil et al showed that the oxygen remote plasma (9 s) could be used for depositing STO films using Sr(METHD) 2 (METHD = methoxyethoxy-tetramethyl-heptanedionate) even at a relatively low temperature (B250 1C) without detectable impurities (detection limit B0.1 at%). [81][82][83][84] Notably, the diketonate Sr precursor, which had been reported not to react with the most common oxygen sources, successfully reacted with remote oxygen plasma.…”
Section: Use Of Plasma (Intra-deposition and Post-deposition)mentioning
confidence: 99%
See 2 more Smart Citations